The simplified follicular lymphoma PRIMA‐prognostic index is useful in patients with first‐line chemo‐free rituximab‐based therapy. (14th May 2020) - Kimby, Eva; Lockmer, Sandra; Holte, Harald; Hagberg, Hans; Wahlin, Björn E.; Brown, Peter; Østenstad, Bjørn
Summary: Follicular lymphoma (FL) is a heterogeneous disease; therefore, reliable prognostic tools are needed to plan treatment strategies. The FL International Prognostic Index (FLIPI) was developed before the rituximab era, while the PRIMA‐PI was built on rituximab chemotherapy. Our objective was to evaluate these two prognostic tools in a cohort of 291 patients with FL treated in two prospective randomised Nordic Lymphoma Group trials with rituximab ± interferon. All patients had symptomatic/progressive disease and were previously untreated. The PRIMA‐PI was prognostic for both time to treatment failure (TTF) and overall survival (OS) (log‐rank P = 0·003 and P < 0·001, respectively). The PRIMA‐PI high‐risk identified a small group of patients with a very short TTF and OS compared to the low‐risk group, with a hazard ratio (HR) of 1·90 (95% confidence interval [CI] 1·30–2·78, P = 0·001) and HR of 3·19 (95% CI 1·75–5·83, P < 0·001), respectively. The FLIPI risk groups were prognostic only for OS (log‐rank P = 0·018). The simplified PRIMA‐PI was valid in our FL cohort with first‐line rituximab‐containing chemo‐free therapy and shows an improved risk stratification compared to the FLIPI, especially in patients aged >60 years. Patients in the PRIMA‐PI high‐risk group should be considered for alternative therapies.